Home Hospital for Orthopaedic Surgery: Opportunities and Challenges of a New Delivery Model. (6th April 2022) - Karhade, Aditya V.; Chen, Antonia F.; Makhni, Melvin C.; Schwab, Joseph H.; Simpson, Andrew K.; Tsai, Thomas C.
Abstract: Home Hospital (HH) is a clinical service involving the delivery of acute inpatient care in the home setting. Acute care services provided via HH include continuous telemonitoring, intravenous fluids and medications, nursing care, point-of-care imaging and laboratory tests, and in-person and virtual clinician visits. Despite offering an inpatient level of care, HH has lower fixed costs and less overhead than conventional hospital settings and offers rapid scalability. Originally implemented for acute medical conditions, HH has proven to be a safe and value-based care-delivery model for a variety of medical conditions, ranging from heart failure to chronic obstructive pulmonary disease exacerbations. For surgical conditions, HH represents an opportunity to reduce adverse hospital-acquired conditions, improve patient and caregiver satisfaction, and decrease cost. The patient profile of orthopaedic surgery inpatients matches that of patients who are most likely to benefit from HH—namely, those who are prone to functional decline, delirium, and nosocomial infections. A focus on surgeon leadership, quality and safety, and digital health with collection of patient-reported outcome measures (PROMs) will ensure that the potential of HH is realized as implementation and widespread rollout proceed.